The Encyclopedia of Theoretical Criminology 2014
DOI: 10.1002/9781118517390.wbetc198
|View full text |Cite
|
Sign up to set email alerts
|

Routine Activity Theory

Abstract: Routine activity theory, first formulated by Lawrence E. Cohen and Marcus Felson (1979) and later developed by Felson, is one of the most widely cited and influential theoretical constructs in the field of criminology and in crime science more broadly. In contrast to theories of criminality, which are centered on the figure of the criminal and the psychological, biological, or social factors that motivated the criminal act, the focus of routine activity is the study of crime as an event, highlighting its rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 12 publications
0
20
0
3
Order By: Relevance
“… Cohen and Felson (1979) suggested that many traditional criminological theories had difficulty explaining the annual changes in crime rate trends after World War II. The theory views crime as an event, emphasizing its relation to space and time and its ecological process ( Miró, 2014 ), rather than focussing on the offender. Structural changes in routine activity patterns offer more opportunities for crime to take place and, Cohen and Felson (1979) argued, can influence crime rates when three elements converge in space and time.…”
Section: Previous Studiesmentioning
confidence: 99%
“… Cohen and Felson (1979) suggested that many traditional criminological theories had difficulty explaining the annual changes in crime rate trends after World War II. The theory views crime as an event, emphasizing its relation to space and time and its ecological process ( Miró, 2014 ), rather than focussing on the offender. Structural changes in routine activity patterns offer more opportunities for crime to take place and, Cohen and Felson (1979) argued, can influence crime rates when three elements converge in space and time.…”
Section: Previous Studiesmentioning
confidence: 99%
“…In addition to demonstrating spatial patterns, crimes have been shown to have seasonal trends [7]. Based on criminological and psychological theory, there is reason to believe that seasonal trends may be related to temperature effects [8,9].…”
mentioning
confidence: 99%
“…A motivated offender is one who is both inclined and able to commit a crime (Felson and Cohen 1980). A suitable target is a person/object which can be threatened by the potential offender (Miro 2014). Lastly, a capable guardian is a person or a thing that can prevent or deter the potential criminal from acting on its evil intentions (Felson and Cohen 1980).…”
Section: A Routine Activity Approachmentioning
confidence: 99%